Achieving excellence in logistics through the appropriate style of information management. - Franz, Peter (My University, 1997)
Logistics is a management discipline that has been spoken about for years and is yet to deliver the full potential that it purports to bring about. Excellence in logistics has been identified as one of the major challenges that products related organisations currently face to ensure continued success in an increasingly competitive, global market. One of the key enablers to integration is the effective application of information technology. Most managers easily accept this as fact but few are clear in describing how this can be achieved. Two prime works used as reference for this research are Bowersox's research into logistics, providing a reference framework on the role of logistics in organisations, and Cilliers's study of logistics at ISO South African companies, providing a South African reference point, It is the combination of the Bowersox attributes and the Cilliers qualified sample of South African companies that provides the basis for an exciting research initiative establishing the role of information technology in achieving logistics excellence in South Africa Both successful and less successful organisations were measured against a set of attributes to determine which were most crucial in achieving logistics excellence: It is clear from the survey that logistics excellent companies have a marked difference in their approach to information teclmology as compared to those who are not logistics excellent. This is mapped out in the paper in some detail and some of the detailed responses may be somewhat of a surprise to the reader as they challenge conventional wisdom. The results of the survey were encapsulated into a simple model. This should act as a quick reference to IT professionals seeking to playa leading role in driving their company towards logistics excellence. Information technology plays a vital role in achieving logistics excellence. This paper provides some insight into the factors that are critical in achieving this goal.
A research report submitted to the Faculty of Commerce, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirement for the degree of Master of Commerce,
Keywords: Management -- Data processing.; Information technology -- Management.; Organizational change.